The Effect of Direct Reading Thinking Activity (DRTA) On Studentsâ Reading Comprehension: An Experimental Study at SMA Negeri 4 Bogor - Lusyani, Fajaria (UICELL, 2017)
The aim of this study was to investigate the effect of directed reading thinking activity (DRTA) on studentsâ reading comprehension at second grade students of SMA Negeri 4 Bogor. The population of this study consisted of 60 secondary grade students at SMA Negeri 4 Bogor. The two groupsâ including pre-post test true experimental design was used in this study. The instrument tools are studentsâ reading score such as pre-test and post-test such as summarizing and responding test; and reading asessment rubric. The result showed that tcalculated is 14.136 with the value of d.f is 58 while the result of  t-table in the level significant t0.05 = 1.684 and t0.01 = 2.423. Since the t-calculated is higher than t-table (4.624 > 1.624 < 2.423), it can be concluded that the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. It is concluded that Directed Reading Thinking Activity (DRTA) effects on studentâs reading comprehension.